Implementation assessment of the Kansas City Design Center proposed Rail Park - Wilbur, Sara E. (Kansas State University, 2012)
From start to finish, implementing large public infrastructure projects, like a park, can be challenging. Funding shortages, public opposition, and physical limitations are all potential problems that can halt a project’s development. This study explores the complexities of implementation by using a proposed park designed by the Kansas City Design Center as a case study for examination. The visioning process, or first stage of implementation, is explored by examining the factors that influenced the design. Through interviews, this report then examines how the actors and processes of project implementation work together or against each other in project development. Applying the learned knowledge of implementation to the proposed park of the Kansas City Design Center presented multiple challenges, as well as opportunities for the park. After understanding implementation and its application to the Rail Park, three main strategies are proposed to move the Kansas City Design Center’s proposed park past the visioning stage. The three strategies are: to collaborate between actors, garner public support, and project phasing. General conclusions about implementation in this study found that there will be challenges and not all can be anticipated, but it is important to plan for those that can be. Being flexible and persistent to move a project forward is necessary in order to accommodate stakeholders’ concerns and unforeseen problems. Knowledge of implementation and its complexities will assist actors, developers, and students to advance visions into reality.
Keywords: Urban park; Public infrastructure; Project implementation; Kansas City Design Center; Implementation process; Area Planning and Development (0341)